SEJARAH DAN PERKEMBANGAN WAKAF DALAM ISLAM - Erianto, Ridho; Nasution, Yenni Samri Juliati (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2023)
Waqf is defined as property belonging to a person or group of people, this property has an eternal nature, it does not run out when used, the property is released by the owner, that the property released cannot be given away, inherited. passed down from generation to generation, or traded, and the benefit of the property is for the public interest in accordance with Islamic teachings. This research is qualitative research using a library study analysis approach with documentation data collection techniques and through written work of a bibliographic nature. This research aims to find out the definition of the meaning of waqf, the history of the development of waqf, and the wisdom of waqf. The mission of waqf is more than just collecting donated assets. Waqf has many benefits for humanity and has various purposes, including providing places of worship, education, medicine and housing in the long term.